Zinc‐induced modulation of SRSF6 activity alters Bim splicing to promote generation of the most potent apoptotic isoform BimS. (3rd June 2013) - Hara, Hirokazu; Takeda, Tatsuya; Yamamoto, Nozomi; Furuya, Keisuke; Hirose, Kazuya; Kamiya, Tetsuro; Adachi, Tetsuo
<x xml:space="preserve">Abstract</x> Bim is a member of the pro‐apoptotic BH3‐only Bcl‐2 family of proteins. Bim gene undergoes alternative splicing to produce three predominant splicing variants (BimEL, BimL and BimS). The smallest variant BimS is the most potent inducer of apoptosis. Zinc (Zn2+) has been reported to stimulate apoptosis in various cell types. In this study, we examined whether Zn2+ affects the expression of Bim in human neuroblastoma SH‐SY5Y cells. Zn2+ triggered alterations in Bim splicing and induced preferential generation of BimS, but not BimEL and BimL, in a dose‐ and time‐dependent manner. Other metals (cadmium, cobalt and copper) and stresses (oxidative, endoplasmic reticulum and genotoxic stresses) had little or no effect on the expression of BimS. To address the mechanism of Zn2+‐induced preferential generation of BimS, which lacks exon 4, we developed a Bim mini‐gene construct. Deletion analysis using the Bim mini‐gene revealed that predicted binding sites of the SR protein SRSF6, also known as SRp55, are located in the intronic region adjacent to exon 4. We also found that mutations in the predicted SRSF6‐binding sites abolished generation of BimS mRNA from the mutated Bim mini‐gene. In addition, a UV cross‐linking assay followed by Western blotting showed that SRSF6 directly bound to the predicted binding site and Zn2+ suppressed this binding. Moreover, Zn2+ stimulated SRSF6 hyper‐phosphorylation. TG003, a cdc2‐like kinase inhibitor, partially prevented Zn2+‐induced generation of BimS and SRSF6 hyper‐phosphorylation. Taken together, our findings suggest that Zn2+ inhibits the activity of SRSF6 and promotes elimination of exon 4, leading to preferential generation of BimS.